Systematic review of efficacy and safety of shorter regimens for drug-resistant tuberculosis (DR-TB) in children - Lovely Jain; Meenakshi Malik; Kulbir Kaur; Sarita Dogra; Abhishek Purohit; Meenakshi Sachdeva; Monica Chaudhry; Pranita Pradhan; Joseph L. Mathew (Clinical Epidemiology and Global Health, 2024)
Introduction: Recent years have witnessed the emergence of antimicrobial-resistant strains of Mycobacterium tuberculosis, resulting in drug-resistant tuberculosis (DR-TB). DR-TB is difficult to treat, necessitating prolonged therapy with multiple medications. However, attempts have been made to shorten the therapeutic regimen in DR-TB. Objective: This systematic review was undertaken to investigate the efficacy and safety of short-term regimens (STRs) for the treatment of DR-TB in children. Methods: We conducted a comprehensive literature search across PubMed, EMBASE, Scopus, CINHAL, Web of Science, Cochrane Library, major trial registries, and grey literature. We searched for randomized controlled trials, and observational studies, comparing World Health Organization (WHO) approved treatment regimens of ≤12 months duration (shorter regimens) versus >12 months duration (longer regimens), in children (<18 years) diagnosed with DR-TB. Data on cure rate, mortality rate, and adverse events were analyzed. Results: From 44,532 records, step-wise screening of titles and abstract identified 90 potentially relevant publications. Full-text screening eliminated 13 (being reviews, reports, oral presentations, or abstracts). Among the remaining 77 (17 RCTs and 60 observational studies), in 21 studies the population did not match the review question, in 33, the intervention was different, and in 23 studies, data on children could not be extracted separately from adults. Thus this systematic review did not identify any RCT or observational study meeting the inclusion criteria. Conclusion: This systematic review did not identify any RCT or observational study on the efficacy and safety of STRs in children with DR-TB. This necessitates urgent generation of robust evidence in this population.